Sejarah Konservasi Mangrove Pantai Cemara, Kecamatan Muncar, Kabupaten Banyuwangi, 1980-an-2020 - Kezia Lilienasanti Pariyanto; Akmal Bakhitah Rabani (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study examines the history of mangrove conservation in Cemara Beach, Muncar District, Banyuwangi Regency, from the 1980s to 2020. The main focus lies on the dynamics of changes in coastal ecosystems due to land conversion into shrimp ponds, as well as the response of the community and government to the destruction of mangrove forests that occurs. The 1980s period became a crucial phase when intensive pond investment began to flourish which had an impact on environmental degradation, especially the loss of most of the natural mangrove vegetation in the region. These changes not only affect the balance of ecosystems, but also impact the livelihoods of coastal communities that depend on the sustainability of natural resources. Since the early 2000s, various conservation initiatives have emerged spearheaded by coastal community groups, students, NGOs, as well as support from government agencies. These conservation efforts are participatory and community-based, reflecting the increased ecological awareness of local communities. This study uses oral history methods and literature studies to reconstruct conservation narratives from the perspectives of local actors directly involved in the process. The results of the study show that the success of mangrove conservation in Cemara Beach is highly dependent on synergy between various actors, ranging from local communities, academics, to government agencies. Policies that support the protection of coastal areas are also an important factor in creating a participatory space for environmental rehabilitation efforts. This conservation history shows the socio-ecological transformation of the coastal communities of Muncar, from an exploitation orientation to a recovery model based on local wisdom. Furthermore, mangrove conservation in Cemara Beach is also the foundation in the development of environment-based ecotourism as well as an example of sustainable natural resource management practices on the southern coast of Banyuwangi.